Simultaneous shade development, antibacterial, and antifungal functionalization of wool using Punica granatum L. Peel extract as a source of textile dye. Issue 4 (19th May 2019) - Shahid, Mohammad; Shahid-ul-Islam,; Rather, Luqman Jameel; Manzoor, Nikhat; Mohammad, Faqeer
ABSTRACT: In this work, we investigated the use of pomegranate peel extract as an effective functional dye for producing beautiful natural shades on wool and to impart durable antimicrobial properties. Wool is treated with various metal salt mordants in the presence of pomegranate dye under optimum natural dyeing conditions. The structural changes of wool are characterized by SEM and FT-IR techniques. The properties of color strength, color fastness to light, washing, rubbing, and durability of antimicrobial activity to washing are investigated. The experimental results indicate that there is small color variation among shades obtained under identical dyeing conditions. Furthermore, it was found that metal salt mordants improved dyeing depth, fastness properties, and effectively enhanced the durability of antimicrobial activity up to several washing cycles.